Beneficial or Detrimental Ignorance: The Straw Man Fallacy of Flyvbjerg's Test of Hirschman's Hiding Hand. (March 2018) - Ika, Lavagnon A.
Highlights: Paper suggests Flyvbjerg knocks down a straw man, not the Hiding Hand. Paper uses a project management lens and a sample of 161 World Bank projects. Paper connects the Hiding Hand and the Planning Fallacy with project performance. Paper finds that the Hiding Hand empirically prevails over the Planning Fallacy. Paper outlines three flaws in Flyvbjerg's test of the Hiding Hand. Summary: In a recent paper in this journal, " The Fallacy of Beneficial Ignorance: A Test of Hirschman's Hiding Hand ", Professor Bent Flyvbjerg claims that there is no such thing as beneficial ignorance and that ignorance is detrimental to project success. Moreover, he argues that if Hirschman's principle of the Hiding Hand were correct, then benefit overruns would exceed cost overruns. Thus, with a statistical test, he demonstrates that the Hiding Hand is in fact less common than its "evil twin", the Planning Fallacy. In this rejoinder, the author shows that Flyvbjerg's test is built on a straw man fallacy and that he fails to refute the Hiding Hand. Contrary to Flyvbjerg—who focuses on the narrow costs and benefits—this paper provides evidence that while the Hiding Hand is found among projects that are project management failures but project successes, the Planning Fallacy fits with projects that are both project management and project failures. On that basis, the author analyzes a sample of 161 World Bank-funded projects of different types and finds that the Hiding Hand prevails. While future research should ascertain this finding, the author then points out the methodological limitations of Flyvbjerg's test. Indeed, it is ironic that the Hiding Hand, a principle crafted against the very idea of cost–benefit analysis, is refuted on that very basis. Even worse, Flyvbjerg, in his cost–benefit analysis, ignores the full life-cycle project costs and benefits, the unintended project effects, the difficulties, and problem-solving abilities so dear to Hirschman, and, thus, treats the management of projects as a kind of "black box". Finally, the author submits that Hirschman was a behavioral project theorist, and argues that it is more important to shed light on the circumstances where the Hiding Hand works than to question whether the principle of the Hiding Hand is right.